The Effect of HOTS-Oriented Blended Learning Student Worksheets on Students' Cognitive Learning Outcomes on Work and Energy Materials - Arca Hatiti; I Wayan Distrik; Undang Rosidin (Universitas Lambung Mangkurat, 2021)
This study aims to determine the effect of HOTS-oriented blended learning student worksheets on students' cognitive learning outcomes on work and energy materials for class X MIPA at SMAN 1 Gadingrejo in the 2020/2021 academic year. The research design used is a quasi-experimental form of nonequivalent control group design. The sample in this study was class X MIPA 5 (experimental class) and class X MIPA 4 (control class). The experimental class was treated using HOTS-oriented blended learning worksheets, while the control class was treated using the HOTS-oriented student worksheets. The test instrument used is in the form of a description of 5 questions. Based on the research results that have been done, the average N-Gain in the experimental class is 0.46 in the medium category. In the control class, the average N-Gain is 0.34 in the medium category. The results of the independent sample t-test showed that the significant value of 0.05 was 0.002. It shows an effect of using HOTS-oriented blended learning student worksheets on students' cognitive learning outcomes on work and energy materials.